2010
DOI: 10.1073/pnas.1009485107
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide analysis reveals mechanisms modulating autophagy in normal brain aging and in Alzheimer's disease

Abstract: Dysregulation of autophagy, a cellular catabolic mechanism essential for degradation of misfolded proteins, has been implicated in multiple neurodegenerative diseases. However, the mechanisms that lead to the autophagy dysfunction are still not clear. Based on the results of a genome-wide screen, we show that reactive oxygen species (ROS) serve as common mediators upstream of the activation of the type III PI3 kinase, which is critical for the initiation of autophagy. Furthermore, ROS play an essential functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
406
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 581 publications
(427 citation statements)
references
References 29 publications
20
406
1
Order By: Relevance
“…Here, we demonstrated that autophagy levels of aged BMMSCs were decreased compared with young BMMSCs. Numerous studies have indicated that with aging, autophagy decreases in different kinds of tissue such as kidney and brain (Kume et al., 2010; Lipinski et al., 2010). There are also studies revealing that autophagy is activated during aging in cells such as fibroblasts (Demirovic, Nizard, & Rattan, 2015) as in aged BMMSCs (Zheng et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that autophagy levels of aged BMMSCs were decreased compared with young BMMSCs. Numerous studies have indicated that with aging, autophagy decreases in different kinds of tissue such as kidney and brain (Kume et al., 2010; Lipinski et al., 2010). There are also studies revealing that autophagy is activated during aging in cells such as fibroblasts (Demirovic, Nizard, & Rattan, 2015) as in aged BMMSCs (Zheng et al., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Dysfunctional autophagy has been observed in aging and age‐related diseases (Levine & Kroemer, 2008; Lipinski et al ., 2010). Autophagy is a homeostatic cellular recycling mechanism responsible for degrading injured or dysfunctional cellular organelles and proteins in all living cells (Mizushima et al ., 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, inhibiting autophagy confers cellular deficits related to aging (Blagosklonny, 2010; Rubinsztein et al ., 2011). Furthermore, autophagy declines during normal aging in Drosophila muscle (Demontis & Perrimon, 2010), mouse lung (Shirakabe et al ., 2016), and human brain (Lipinski et al ., 2010), and the mitochondrial autophagy (mitophagy) inducer PINK1 is transcriptionally downregulated during aging in mouse lung (Sosulski et al ., 2015). It was previously proposed that IIS pathway activity is deleterious to old organisms via inhibition of autophagy (Blagosklonny, 2010; Gems & de la Guardia, 2012).…”
Section: Iis Pathway Activity Increases Protein Translation and Inhibmentioning
confidence: 99%
“…Autophagy declines during normal aging in Drosophila muscle (Demontis & Perrimon, 2010), rat liver (Del Roso et al ., 2003); mouse lung (Shirakabe et al ., 2016), and human brain (Keller et al ., 2004; Lipinski et al ., 2010). Finally, the mitophagy inducer PINK1 is transcriptionally downregulated during aging in mouse lung (Sosulski et al ., 2015).…”
Section: Testing Predictions Of This Modelmentioning
confidence: 99%